Bacterial Colonization on Different Suture Materials Used in Oral Implantology: A Randomized Clinical Trial - Nima Nadafpour (Frontiers in Dentistry, 2021)
Objectives: This study aimed to compare the colonization of Enterococcus faecalis (E. faecalis), Escherichia coli (E. coli), Streptococcus mutans (S. mutans) and Staphylococcus aureus (S. aureus) isolated from the oral cavity on different suture materials used in oral implantology.